Ketiadaan Peran Ayah (Fatherless) terhadap Perkembangan Kepribadian dan Regulasi Emosi Anak - Rafi Alqifary; Sri Nurhayati Selian (HARAPAN: Jurnal Ilmu Kesehatan dan Psikologi, 2026)
This study aims to examine how the absence of a father figure (fatherlessness) influences children's personality development and emotional regulation. Fatherlessness has become an increasingly significant issue in contemporary family studies, as the father's role extends beyond economic support to include emotional guidance, socialization, and the formation of children's psychological well-being. The absence of paternal involvement may hinder children's ability to regulate emotions, establish healthy interpersonal relationships, and develop positive self-concepts. This research employed a qualitative approach using a case study design. Data were collected through in-depth semi-structured interviews with three participants who experienced fatherlessness during their developmental years. The collected data were analyzed using thematic analysis to identify recurring patterns, meanings, and experiences related to emotional regulation and personality development. The findings indicate that the absence of a father figure contributes to emotional instability, reduced self-confidence, weakened self-control, feelings of insecurity, and challenges in building meaningful social relationships. Participants also reported experiencing greater vulnerability to stress and difficulties in managing negative emotions. Nevertheless, the study reveals that these adverse effects can be mitigated through the presence of supportive substitute figures, such as mothers, grandparents, extended family members, teachers, or mentors, as well as positive social environments that provide emotional security and consistent guidance. The study concludes that a father's presence plays a crucial role in fostering healthy personality development and effective emotional regulation. However, supportive family and community environments can function as protective factors that help children adapt and develop resilience despite experiencing fatherlessness.